Metagenomes, Metatranscriptomes, and Metagenome-Assembled Genomes from Chesapeake and Delaware Bay (USA) Water Samples - Ahmed, Mir Alvee (Microbiol Resour Announc, 2021)
Here, we present 36 metagenomes, 59 metatranscriptomes, and 373 metagenome-assembled genomes (MAGs) from Chesapeake and Delaware Bay water samples. This data set will be useful for studying microbial biogeochemical cycling in estuaries.